Affordable Value Innovation: Study in Education Industry in Indonesia - Kurnia, Pepey Riawati (JURNAL ILMU MANAJEMEN, 2025)
Previous research suggests that FMCG companies in Indonesia do not pay attention to and consider the two antecedent factors in the Affordable Value Innovation (AVI) process. The Standardization factor has a positive effect on AVI (Ardes & Ardana, 2017). The research test on the fourth antecedent factor shows that Corporate Culture of Innovation (CCOI) does not affect AVI. The findings indicate that FMCG companies in Indonesia do not focus on and consider CCOI in the AVI process, and the AVI affects the IP variable. The research was continued using the same model for the education industry in Indonesia. No research has been conducted using this model for the education industry in Indonesia. Data collection resulted in 31 respondents from the student innovation project unit of STM PPM and Trisakti University. The research data were processed using SMART PLS. The research findings in the Indonesian education industry suggest that there are 2 antecedent factors (local embeddedness and standardization) influencing the AVI, which affects the IP. Indonesian local innovation, standards, and affordable prices affect the innovation performance carried out in education.